Spatial and temporal variations of particulate organic matter from Moselle River and tributaries: A multimolecular investigation. (August 2017) - Le Meur, Mathieu; Mansuy-Huault, Laurence; Lorgeoux, Catherine; Bauer, Allan; Gley, Renaud; Vantelon, Delphine; Montargès-Pelletier, Emmanuelle
Highlights: SPM was collected along the Moselle River and for different regime flow and seasons. SPM organic markers from the lipid and refractory fractions characterized. Fensch River showed greater microbial contribution, highlighting urbanized areas. The regime flow engendered OM content decrease and more degraded OM. Seasonal variations, recorded with high autochthonous contribution during summer. Abstract: The spatial and temporal composition of organic matter (OM) was investigated in the Moselle watershed (Lorraine, France). The spatial composition was studied using different stations along the river and four tributaries. In addition, one anchor station was used in order to better understand the temporal OM composition during different hydrologic regimes and seasons. The first part of the organic characterization consisted of the extraction of the lipid. OM with an automatic extractor. The extracts were analyzed for their lipid fatty acids (Lip-FAs), polycyclic aromatic hydrocarbons (PAHs) and sterols using gas chromatography-mass spectrometry (GC–MS). The insoluble fraction was also analyzed with thermochemolysis-GC–MS (TMH-GC–MS) using tetramethylammonium hydroxide (TMAH) and lignin phenols, permethylated deoxy aldonic acids and refractory FAs (Ref-FAs) were analyzed. The results showed that one station (Florange station) on the small Fensch stream tributary displayed variation in the composition of the molecular OM, with higher microbial markers (C16:1, C18:1w7, C18:1w9, coprostanol) inputted to the highly industrialized and urbanized areas in this small sub-catchment. The other stations showed rather similar organic composition (Lip-FAs, Ref-FAs, sterols, lignin compounds, PAHs) due to the size of the catchment (10, 000 km 2 ) or the integrative state of the suspended particulate matter (SPM). The regime flow involved a decrease in SPM OM content as well as a decrease in the palmitoleic acid/palmitic acid (C16:1 /C16:0 ) ratio and an increase in the (stigmastanol + sitostanol + stigmasterol + sitosterol)/(cholesterol + cholestenol) (C29 /C27(ST) ) ratio, revealing the presence of more allochthonous OM. The increase in regime flow was also correlated with a growing contribution of more degraded OM to the SPM that could be related to the leaching of subsurface soils from the watershed or to the remobilization of surface sediments. Seasonal variations were also observed, with a stronger contribution of autochthonous production during low flow level in summer. The work shows the importance of OM characterization of SPM in order to better assess the spatial and temporal OM variation in the water column.